PENGARUH FUNGSI KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SMP NEGERI 2 TEMBILHAN KABUPATEN INDRAGIRI HILIR - jurnalmap map; Muhamad Nurlin (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
This study aims to describe the influence of the principal's leadership function on the performance of teachers at SMP Negeri 2 Tembilahan, Indragiri Hilir Regency. The study population included all 35 Tembilahan Junior High School teachers, who were also the study sample. Data collection is done by questionnaire. Then the data were analyzed with multiple regression analysis techniques. The results showed that partially the principal's leadership function consisting of the educator function, manager function, administrator function, supervisor function, innovator function and motivator function significantly influence teacher performance. The motivator function is the dominant variable influencing the performance of teachers in SMP Negeri 2 Tembilahan, Indragiri Hilir Regency. Simultaneously the leadership function of the principal consisting of the educator function, manager function, administrator function, supervisor function, innovator function and motivator function significantly influences the performance of teachers in SMP Negeri 2 Tembilahan, Indragiri Hilir Regency. Keywords: teacher performance, school principal's leadership function